Small Supernumerary Marker Chromosome May Provide Information on Dosage-insensitive Pericentric Regions in Human - Hamid Al-Rikabi, Ahmed B.; Pekova, Sona; Fan, Xioabo; Jancuskova, Tereza; Liehr, Thomas (Current Genomics, 2018)
Background: Cytogenetically visible chromosomal imbalances in humans are deleterious and adverse in the majority of the cases. However, healthy persons living with chromosomal imbalances in the range of several megabasepairs (Mbps) in size, like carriers of small Supernumerary Marker Chromosomes (sSMCs) exist. Materials & Methods: The identification of healthy sSMC carriers with euchromatic centromere-near (ECN) imbalances led to the following proposal: ECN-regions do not contain any dosage sensitive genes. Due to own previous work, dosage-insensitive pericentric ECN-regions were already determined with an accuracy of 0.3 and 5 Mbp. Based on this data we established 43 new pericentromeric probe sets spanning about 3-5 Mbp of each euchromatic human chromosome arm starting from the known insensitive regions towards distal. Such so called pericentromeric-critical region fluorescence in situ hybridization (PeCR-FISH) probe sets were applied exemplarily and successful here in 15 sSMC cases as available from the Else Kröner-Fresenius-sSMC-cellbank http://ssmc-tl.com/ekf-cellbank.html. Conclusion: Most of the involved sSMC breakpoints could be characterized as a higher resolution than before. An unexpected result was that in 5/15 cases cryptic mosaicism was characterized. The latter is also to be considered to have potentially an influence on the clinical outcome in these so-called discontinuous sSMCs. Overall, the suitability of PeCR-FISH to characterize sSMCs was proven; the potential of this probe set to further delineate sizes of dosage insensitive pericentric regions is obvious but dependent on suited cases. Furthermore, discontinuous sSMCs can be identified by this approach and this new subtype of sSMC needs to be studied in more detail in future.
Keywords: Molecular cytogenetics